Pengaruh Keselamatan Dan Kesehatan Kerja Serta Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan - Jean Rosalina Asthenu; Victor R. Pattipeilohy (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2022)
Employee productivity of PT. NengmeyPratama Malut Maluku (NMM) Ternate Branch in carrying out work is decreasing (low), this is due to the lack of employee knowledge about occupational safety and health and inadequate facilities in the work environment. The purpose of this paper is to examine the work productivity of employees and at the same time provide solutions for improvement. The method used is quantitative analysis in the form of theoretical studies and expert opinions about maximum employee productivity. The results showed that the work productivity of employees of PT. NengmeyPratama Malut Maluku (NMM) Ternate Branch is not optimal. To increase the work productivity of employees of PT. NengmeyPratama Malut Maluku (NMM) Ternate Branch can be done by conducting socialization to employees about occupational safety and health, and paying attention to facilities in the work environment in the form of K3 equipment in carrying out employee work so that an increase in employee productivity is expected. Keywords: 1) Occupational Health and Safety; 2) Work Environment; 3) Productivity